Contemporary world regional geography global connections, local voices - Bradshaw, Michael J. (McGraw-Hill/Irwin, 2007)
Provides geographical study of world issues through analysis of nine world regions and the countries in each. This book integrates the themes of "global connections" and "local voices". It discusses the global and local tensions, as well as economic, political, cultural, social, and environmental issues.